MUSICA COMMUNITAS INTERCULTURALIS - międzynarodowe festiwale i wymiany kulturalne dzieci i młodzieży jako przykłady budowania międzykulturowej wspólnoty muzycznej = MUSICA COMMUNITAS INTERCULTURALIS - international festivals and cultural exchanges of children and young people as examples of building cross-cultural community of music - Dziadowiec, Joanna (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
This article presents examples of building/co-creating musical culture through youth cultural exchanges commonly referred as "the meetings of cultures": 1). intercultural folkloristic exchanges of groups of different types, often accompanied by participation in local festivals (in the form of a competition or review); 2). cultural exchanges of music schools.
Keywords: kultura muzyczna; wymiana międzykulturowa; edukacja międzykulturowa; kultura organizacyjna; dialog międzykulturowy; music culture; intercultural exchange; intercultural education; organizational culture; cross-cultural dialogue